Climate risk management in Central Asian agriculture: A situation analysis - Ira Pawlowski (Justus-Liebig-Universität Gießen, Zentrum für Internationale Entwicklungs- und Umweltforschung (ZEU), 2012)
The region of Central Asia, and in particularly the agricultural sector, is extremely vulnerable to climate change risks. The countries have started to develop adaptation strategies and climate risk management strategies, most of them described in the National Communications on the United Nations Framework Convention on Climate Change. These and other efforts are presented and commented in this paper.
Keywords: 330; climate change; climate risk management; Central Asia